Synthesis of the Icetexane Diterpenoids (±)-Rosmaridiphenol, (±)-Pisiferin, and (±)-Barbatusol from Abietane - Le, Thuy Quynh; Lee, JuHui; Oh, Chang Ho (Synlett, 2022)
We report the rearrangement of abietane core with trifluoromethanesulfonic anhydride in pyridine to afford the icetexane core, a key intermediate for total syntheses of the structurally intriguing and biologically active compounds (±)-barbatusol, (±)-rosmaridiphenol, and (±)-pisiferin.
Keywords: icetexane; abietane; diterpenoids; pisiferin; rosmaridiphenol; barbatusol; ring expansion